Use of Physical Therapy Following Total Knee Replacement Surgery: Implications of Orthopedic Surgeons' Ownership of Physical Therapy Services. (23rd February 2016) - Mitchell, Jean M.; Reschovsky, James D.; Reicherter, Elizabeth Anne
Abstract : Objective: To examine whether the course of physical therapy treatments received by patients who undergo total knee replacement (TKR) surgery differs depending on whether the orthopedic surgeon has a financial stake in physical therapy services. Data: Sample of Medicare beneficiaries who underwent TKR surgery during the years 2007–2009. Study Design: We used regression analysis to evaluate the effect of physician self‐referral on the following outcomes: (1) time from discharge to first physical therapy visit; (2) episode length; (3) number of physical therapy visits per episode; (4) number of physical therapy service units per episode; and (5) number of physical therapy services per episode expressed in relative value units. Principal Findings: TKR patients who underwent physical therapy treatment at a physician‐owned clinic received on average twice as many physical therapy visits (8.3 more) than patients whose TKR surgery was performed by a orthopedic surgeon who did not self‐refer physical therapy services ( p < .001). Regression‐adjusted results show that TKR patients treated at physician‐owned clinics received almost nine fewer physical therapy service units during an episode compared with patients treated by nonself‐referring providers ( p < .001). In relative value units, this difference was 4 ( p < .001). In contrast, episodes where the orthopedic surgeon owner does not profit from physical therapy services rendered to the patient look virtually identical to episodes where the TKR surgery was performed by a surgeon nonowner. Conclusions: Physical therapists not involved with physician‐owned clinics saw patients for fewer visits, but the composition of physical therapy services rendered during each visit included more individualized therapeutic exercises.